Integrating servitisation into the halal supply chain: a roadmap for sustainable business growth - Ibrahim Saleh, Hassan; Fernando, Yudi (Emerald Publisher, 2025)
Purpose The limited existing literature on the future research direction regarding how servitisation and the halal supply chain interact motivates this study. The paper aims to integrate servitisation into the halal supply chain by proposing an integration roadmap for successful adoption in the halal industry.